Analysis of collection development at the National Library of Medicine. - Craig, D F (1980)
This paper reports the major findings of a study of collection development activities at the National Library of Medicine (NLM) from 1965 to 1977. The CATLINE file was the source of the data; analyses were performed on classification number, date of entry, and language. An overview analysis of the data base is presented for major subject and form classes. An in-depth subject analysis of the monograph collection was performed using the NLM call number. An analysis by date of entry revealed that the subject content of CATLINE has varied only slightly over the years; the most notable change was a recent decline in the related and peripheral subject areas. The language analysis indicated that 83% of the data base consisted of works published in English, German, Russian, and French. Throughput processing time was measured for English language monographs for selected years.